The art and science of communication : - Perkins, P. S. (John Wiley & Sons, 2008)
This book will teach you how to: Merge the science of communication with practical, everyday communication occurrences within the workplace in an understandable, applicable and powerfully inspiring way ; Provide tangible practices which when engaged produce results ; Introduce the reader to the rules of Communication in their distinct settings by examining the major, everyday situations employees and employers find themselves in ; Introduce the reader to the first and primary communication experience – the self and the impact of Intrapersonal Communication on ALL aspects of the communication experience ; Show a direct and manageable connection between the variety of communication contexts we all experience and how they build one upon the other